Inflammatory Dilated Cardiomyopathy in Abcg5-deficient Mice. (August 2013) - Wilson, Dennis W.; Oslund, Karen L.; Lyons, Bonnie; Foreman, Oded; Burzenski, Lisa; Svenson, Karen L.; Chase, Thomas H.; Shultz, Leonard D.
Dilated cardiomyopathy (DCM) in A/J mice homozygous for the spontaneous thrombocytopenia and cardiomyopathy ( trac ) mutation results from a single base pair change in the Abcg5 gene. A similar mutation in humans causes sitosterolemia with high plant sterol levels, hypercholesterolemia, and early onset atherosclerosis. Analyses of CD3+ and Mac-3+ cells and stainable collagen in hearts showed inflammation and myocyte degeneration in A/J- trac/trac mice beginning postweaning and progressed to marked dilative and fibrosing cardiomyopathy by 140 days. Transmission electron microscopy (TEM) demonstrated myocyte vacuoles consistent with swollen endoplasmic reticulum (ER). Myocytes with cytoplasmic glycogen and irregular actinomyosin filament bundles formed mature intercalated disks with normal myocytes suggesting myocyte repair. A/J- trac/trac mice fed lifelong phytosterol-free diets did not develop cardiomyopathy. BALB/cByJ- trac/trac mice had lesser inflammatory infiltrates and later onset DCM. BALB/cByJ- trac/trac mice changed from normal to phytosterol-free diets had lesser T cell infiltrates but persistent monocyte infiltrates and equivalent fibrosis to mice on normal diets. B- and T-cell-deficient BALB/cBy- Rag1 null trac/trac mice fed normal diets did not develop inflammatory infiltrates or DCM. We conclude that the trac/trac mouse has many features of inflammatory DCM and that the reversibility of myocardial T cell infiltration provides a novel model for investigating the progression of myocardial fibrosis.